Exploring the experiences and perceptions of speech language therapists regarding fussy eating in children - Ebrahim, Zeenat (My University, 2016)
Background: Fussy eating has become an increasing concern in paediatric care as a result of its far-reaching consequences for the developing child. However, there is currently a scarcity of published literature related to fussy eating internationally and even more so within the South African context, resulting in a lack of consensus regarding the definition of fussy eating. Aim: To explore the experiences and perceptions of SLTs with regards to fussy eating in children. Methods: The study was based on an exploratory, descriptive, qualitative research design. Data was gathered within semi-structured, in-depth interviews from 30 SLTs who consented to participate in the study. The data was analysed qualitatively, using thematic content analysis. Results: Fussy eating was described as a multi-factorial and heterogeneous condition arising from a number of inter-related aetiologies. The role of sensory integration was noteworthy in the understanding of fussy eating in children, and extended to almost every aspect of the study. The nature of fussy eating described within this study therefore appeared to lend to a multidisciplinary approach to adequately address the needs of this population. The findings of the study further indicated that socio-economic status contributed to the causes of fussy eating. Conclusion: Based on the findings of the study in conjunction with the literature pertaining to fussy eating, a working definition of fussy eating is proposed. The complexity of fussy eating calls for collaboration between healthcare professionals in dealing with this condition. All professionals dealing with fussy eating must therefore be adequately trained to deal with this condition adequately. Key Words: Fussy Eating, Feeding Disorders, Sensory Integration, South Africa
Submitted in fulfilment of the Requirements for Degree of Master of Speech Pathology: The Discipline of Speech Pathology School of Human and Community Development Faculty of Humanities University of the Witwatersrand
Keywords: Fussy eating; Feeding disorders; Sensory integration; South Africa